2012
DOI: 10.1093/neuonc/nos060
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium-186 liposomes as convection-enhanced nanoparticle brachytherapy for treatment of glioblastoma

Abstract: Although external beam radiation is an essential component to the current standard treatment of primary brain tumors, its application is limited by toxicity at doses more than 80 Gy. Recent studies have suggested that brachytherapy with liposomally encapsulated radionuclides may be of benefit, and we have reported methods to markedly increase the specific activity of rhenium-186 ((186)Re)-liposomes. To better characterize the potential delivery, toxicity, and efficacy of the highly specific activity of (186)Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 24 publications
2
72
0
Order By: Relevance
“…294 In this way, recent studies suggest that brachytherapy with liposomally encapsulated 186 Re or 188 Re isotopes holds significant promise for glioma therapy. 229,242,245 These studies demonstrated that animals treated with 186 Re or 188 Re liposomes had significantly prolonged survival, independent of the route of administration. 229,242 Also, 188 Re liposomes have been explored for diagnostic evaluation, revealing the potential of these liposomes as a future theranostic agent for brain gliomas.…”
Section: Design Of Liposomal Drug-delivery Systems For Glioma Therapymentioning
confidence: 89%
See 1 more Smart Citation
“…294 In this way, recent studies suggest that brachytherapy with liposomally encapsulated 186 Re or 188 Re isotopes holds significant promise for glioma therapy. 229,242,245 These studies demonstrated that animals treated with 186 Re or 188 Re liposomes had significantly prolonged survival, independent of the route of administration. 229,242 Also, 188 Re liposomes have been explored for diagnostic evaluation, revealing the potential of these liposomes as a future theranostic agent for brain gliomas.…”
Section: Design Of Liposomal Drug-delivery Systems For Glioma Therapymentioning
confidence: 89%
“…229,242,245 These studies demonstrated that animals treated with 186 Re or 188 Re liposomes had significantly prolonged survival, independent of the route of administration. 229,242 Also, 188 Re liposomes have been explored for diagnostic evaluation, revealing the potential of these liposomes as a future theranostic agent for brain gliomas. 245 A wide variety of liposome-encapsulated anticancer drugs have also been developed for both experimental and clinical oncology.…”
Section: Design Of Liposomal Drug-delivery Systems For Glioma Therapymentioning
confidence: 89%
“…Due to the short path length of 186 Re, the behavior of this nanoconstruct was monitored with SPECT/CT imaging and gamma camera after radiolabeling with 99m Tc. Results showed no overt toxicity of surrounding tissues even at high doses [110]. Aptes-functionalized SPIO nanoparticles were modified with the N-hydroxysuccinimide (NHS) ester of polyethylene glycol maleimide (NHS-PEG-Mal).…”
Section: Rhenium-186 188mentioning
confidence: 99%
“…In recent in vitro or in vivo studies, they were used for the delivery of cytostatic drugs [57][58][59][60], cytotoxic peptides [61], antibodies [62,63], siRNA [64] or even oncolytic viruses [65], to deliver irradiation [66] or to improve imaging techniques [67]. The frame of this paper does not allow to discuss these new therapeutic opportunities in detail.…”
Section: Other Approachesmentioning
confidence: 99%